The Use of Gesture to Overcome Misunderstanding in Teaching English - Rica Umrina Lubis (Journal of English Education and Linguistics, 2022)
Gesture is a type of non-verbal communication that is very influential in teaching and learning activities and interactions between teachers and students. It is not only can convey the speakers’ intention more specifically and adequately, clarify the teaching instruction, encourage the students’ interest, maximize English teaching’s goal but also can help improve the students’ skill in speaking, writing, reading and listening . This study aims to improve students' speaking, writing, reading, listening and interest in English lessons through the use of gestures at SMA Negeri 1 Batang Natal.The method used was descriptive qualitative. The subjects were 2 teachers and 25 students of 11th grade of SMA Negeri 1 Batang Natal The research instruments used were interviews and observations. The results of this study suggests that the use of movement has positive and negative sides for students. The positive side is that the teacher must be able to use the right movements according to the needs of their students. Creating a comfortable atmosphere and considering the most effective method so that students are activated in participating the lessons. While negative side was using too many movements or being too serious when teaching would not create a comfortable classroom atmosphere.